2017
DOI: 10.1080/20008198.2017.1322892
|View full text |Cite
|
Sign up to set email alerts
|

Negative body experience in women with early childhood trauma: associations with trauma severity and dissociation

Abstract: Background: A crucial but often overlooked impact of early life exposure to trauma is its far-reaching effect on a person’s relationship with their body. Several domains of body experience may be negatively influenced or damaged as a result of early childhood trauma. Objective: The aim of this study was to investigate disturbances in three domains of body experience: body attitude, body satisfaction, and body awareness. Furthermore, associations between domains of body experience and severity of trauma symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
5
23
0
2
Order By: Relevance
“…When tentatively comparing our findings with studies of the DBIQ in patients with mixed mental disorders [ 48 ], women with childhood trauma [ 49 ], and patients with depressive disorder [ 50 ], especially the relatively low scores on vitality for patients with somatoform disorder are noteworthy. Scores on sexual fulfilment and self-aggrandizement tend to be lower than those of the mental disorders group [ 48 ] but higher than the scores of the childhood trauma group [ 49 ], while scores on body acceptance and physical contact are about the same as in the mixed mental disorders group. Overall, body image scores appear to be about similar to scores of a sample of patients with mixed mental disorders, with lower vitality scores as the most distinct main outstanding feature in patients with somatoform disorder, especially in patients with pain disorder and undifferentiated somatoform disorder.…”
Section: Discussionsupporting
confidence: 52%
“…When tentatively comparing our findings with studies of the DBIQ in patients with mixed mental disorders [ 48 ], women with childhood trauma [ 49 ], and patients with depressive disorder [ 50 ], especially the relatively low scores on vitality for patients with somatoform disorder are noteworthy. Scores on sexual fulfilment and self-aggrandizement tend to be lower than those of the mental disorders group [ 48 ] but higher than the scores of the childhood trauma group [ 49 ], while scores on body acceptance and physical contact are about the same as in the mixed mental disorders group. Overall, body image scores appear to be about similar to scores of a sample of patients with mixed mental disorders, with lower vitality scores as the most distinct main outstanding feature in patients with somatoform disorder, especially in patients with pain disorder and undifferentiated somatoform disorder.…”
Section: Discussionsupporting
confidence: 52%
“…Since no study specially reported on the body-related clinical characteristics, future research is also required to explore whether individuals with ID experience body-related clinical characteristics following sexual abuse, similar to those experienced by individuals with average IQ or above. Since, Scheffers et al (2017) found that several domains of body experience, such as body attitude, body satisfaction and body-awareness, are often negatively associated with traumatic events, further research should be carried out to explore if and how sexual abuse is associated with these domains in individuals with ID. In addition, whether individuals with ID who have experienced sexual abuse develop feelings of hate towards their body (Fallon & Ackard, 2002) and experience reduced physical vitality and feelings of health (Sack et al, 2010) deserve also to be studied.…”
Section: Implications For Researchmentioning
confidence: 99%
“…They either deny having inner signals or are overwhelmed by these signals (Van der Kolk, 2006). In addition, Scheffers et al (2017) found that traumatic events, such as sexual abuse, not only negatively influences this form of body awareness but also affects the way in which the body is experienced in terms of satisfaction with and attitude towards the body. More specifically, victims of sexual abuse frequently develop feelings of hate towards their body (Fallon & Ackard, 2002) and experience reduced physical vitality and health (Sack, Boroske-Leiner, & Lahmann, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of undergoing a traumatic event are complex and may affect individuals by increasing the risk for many health conditions as drug abuse, diabetes, cancer, heart and respiratory diseases and obesity among others [2][3][4] as well as the individual's relationship with their own body [5,6]. In their study on the link between childhood trauma and dissociation, Scheffers et al (2017) concluded that childhood trauma seriously affected the patient's relationship with their body (body attitude, body satisfaction and body awareness). Consequently, traumatized people can find it difficult to detect internal sensations and perceptions, and sometimes even deny any somatic awareness [5,6].…”
Section: Introductionmentioning
confidence: 99%